2022
DOI: 10.3390/agronomy12020467
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Characterization of a Bacillus Strain for Potential Application in Industrial Production of White Button Mushroom (Agaricus bisporus)

Abstract: White button mushroom—Agaricus bisporus (J.E.Lange) Imbach—is among the most popular cultivated mushrooms worldwide. The most serious challenge in industrial mushroom production is the green mold disease caused by Trichoderma species. Our aim was to isolate and examine bacterial strains from mushroom casing material for their potential use as biocontrol agents. Twenty-seven bacterial strains were isolated and tested against mold pathogens of white button mushroom. The Bacillus velezensis strain SZMC 25431 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The shift in the relative abundance of those indicator genera shows that dazomet treatment not only reduces the relative abundance of SCK indicator genera but also increases the relative abundance of SDT indicator genera ( Figure 8B ). It is interesting that the indictor genera of SDT were beneficial to edible mushrooms because several studies have demonstrated that Micromonospora , Bacillus , and Streptomyces species function in biocontrol, plant growth promotion, and mushroom composting ( Sahin, 2005 ; Hirsch and Valdés, 2010 ; Sotoyama et al, 2016 ; Stanojević et al, 2019 ; Büchner et al, 2022 ). Because the SCK indicator genera, including Candidatus Udaeobacter , Unclassified Xanthobacteraceae , Unclassified Vicinamibacteraceae , and unclassified Vicinamibacterales , could not be identified accurately, their effects on morel growth could not be determined.…”
Section: Resultsmentioning
confidence: 99%
“…The shift in the relative abundance of those indicator genera shows that dazomet treatment not only reduces the relative abundance of SCK indicator genera but also increases the relative abundance of SDT indicator genera ( Figure 8B ). It is interesting that the indictor genera of SDT were beneficial to edible mushrooms because several studies have demonstrated that Micromonospora , Bacillus , and Streptomyces species function in biocontrol, plant growth promotion, and mushroom composting ( Sahin, 2005 ; Hirsch and Valdés, 2010 ; Sotoyama et al, 2016 ; Stanojević et al, 2019 ; Büchner et al, 2022 ). Because the SCK indicator genera, including Candidatus Udaeobacter , Unclassified Xanthobacteraceae , Unclassified Vicinamibacteraceae , and unclassified Vicinamibacterales , could not be identified accurately, their effects on morel growth could not be determined.…”
Section: Resultsmentioning
confidence: 99%
“…(HX0037, HX0016, and HX0039) exhibited outstanding inhibitory activity against Trichoderma FZ0005, suggesting that they might serve as potential biological resources for the biocontrol of ‘Sanghuang’ diseases. As reported in other studies, the use of biofungicides based on Bacillus species could be regarded as a biological alternative to synthetic fungicides employed in mushroom production [ 20 , 70 ]. We suggest that a bacterial suspension of Bacillus strains with antifungal activity against Trichoderma FZ0005 should be sprayed onto the cultivation soil or the surface of bag-cultivated ‘Sanghuang’ mushrooms during propagation and at the stage of fruiting body formation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have also revealed that there are close symbiotic relationships between soil microbes and mushrooms. For example, many soil microbes can attack fruiting bodies at various stages of mushroom growth, producing distinct disease symptoms [ 17 , 18 ], while certain beneficial species such as Pseudomonas and Bacillus can significantly improve crop total fresh matter yield and shorten harvesting time [ 19 , 20 ]. In recent decades, studies on soil microbial community structure have been reported for many crops [ 21 , 22 ], while ‘Sanghuang’ mushroom has mostly been studied for its pharmacodynamic elements and their effects [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The HPLC-HESI-MS/MS examinations of the different surfactin molecules were carried out based on the work of Büchner et al [ 42 ]. The applied instrument was a Nexera XR HPLC system containing a DGU-20A5R degasser, an LC-20ADXR pump, a SIL-20AXR autosampler and a CTO-10ASVP column oven (Shimadzu Corporation, Kyoto, Japan), coupled with a TSQ Quantum Access triple quadrupole mass spectrometer (Thermo Scientific, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%